2017
DOI: 10.1111/jiec.12578
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Concentrations of Ultrafine Particles and Volatile Organic Compounds Resulting from Desktop 3D Printer Operation and the Impact of Potential Control Strategies

Abstract: SummaryRecent studies have shown that potentially hazardous volatile organic compounds (VOCs) and ultrafine particles (UFPs) are emitted from many desktop three-dimensional printer and filament combinations. We use recently published measurements of UFP and speciated VOC emission rates from a number of desktop 3D printers and filaments to predict the magnitudes of human exposures to airborne pollutants that would be expected in multiple locations within a typical small office environment. We also model the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
(59 reference statements)
0
36
1
Order By: Relevance
“…Most of these studies use acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) filaments and in general ABS leads to higher VOC emission (more than half as styrene). To reduce exposure, enclosing printers and installing high-efficiency particulate air (HEPA) filters at exhaust have been suggested [31], among other strategies [32]. One pilot study has also confirmed the operator's exposure to metal particles during powder handling and laser sintering [33].…”
Section: Occupational Health Issuementioning
confidence: 99%
“…Most of these studies use acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) filaments and in general ABS leads to higher VOC emission (more than half as styrene). To reduce exposure, enclosing printers and installing high-efficiency particulate air (HEPA) filters at exhaust have been suggested [31], among other strategies [32]. One pilot study has also confirmed the operator's exposure to metal particles during powder handling and laser sintering [33].…”
Section: Occupational Health Issuementioning
confidence: 99%
“…Mendes and colleagues () characterize emissions from a low‐end 3D printer based on the extrusion of polymers, showing that the process emits nanoparticles inside the chamber, and negligible emissions in room experiments, with emission rates depending strongly on extruder temperature. Following a similar rationale, the article by Azimi and colleagues () predicts the magnitudes of human exposures to airborne pollutants originating from low‐end AM systems that would be expected in multiple locations within a typical small office environment. The results reached demonstrate that emission concentrations within proximity to some systems can exceed recommended exposure levels.…”
Section: The Special Issue: Charting Impacts Across the Product Life mentioning
confidence: 99%
“…The investigation of these phenomena, which may all pose potential health risks, will require tailored approaches due to the large number of AM processes, build parameters, and materials. Three articles in this Special Issue address these topics (Graff et al 2017;Mendes et al 2017;Azimi et al 2017).…”
Section: Health and Safety Considerationsmentioning
confidence: 99%
“…Some papers in this special issue advance this line of research (see, e.g., Yang et al 2017;Gutowski et al 2017 Mami et al 2017). It is hoped that the papers on emissions from 3D printing (Bours et al 2017;Azimi et al 2017;Graff et al 2017;Mendes et al 2017) and unit energy consumption will contribute building blocks to future LCA and other systems-oriented work that is typical of IE. The special issue nonetheless provides insights on topics central to IE such as the impact of 3D printing on supply chains (Holmström and Gutowski 2017) and localization of production enabled by 3D production from an environmental perspective (Cerdas et al 2017;Holmström and Gutowski 2017).…”
mentioning
confidence: 93%